Vitamin E supplementation benefits in Hipercholesterolemic rats - Oré Sifuentes, Raquel (2001)
OBJECTIVE: To assess the vitamin E protective effects against free radicals generation, as it is involved in atheroma plate formation. MATERIAL AND METHODS: We used adult Sprague-Dawley rats as experimental models during three months, arranged into four groups: 1) Control diet group; 2) Control diet plus vitamin E (500 mg/Kg of food) group; 3) cholesterol-rich diet (3%) plus vitamin E group, and 4) cholesterol-rich diet group. Lipid profile and lipid peroxidation were measured both in serum and aortic tissue. RESULTS: The cholesterol-rich diet caused a significant increase (p <0,05) in serum triglycerides, and total and LDL cholesterol levels and a significant decrease in HDL cholesterol (p <0,005) levels despite vitamin E (12 mg/day) supplementation. Group IV showed a significant increase (p <0,005) in lipid peroxidation in serum and aortic tissue. CONCLUSIONS: Vitamin E provided protection against both serum and aortic tissue lipid peroxidation but does not improve the lipid profile.